Low-dose Aspirin for the Prevention of Preterm Delivery in Nulliparous Women With a Singleton Pregnancy (ASPIRIN): A Randomized, Double-blind, Placebo-controlled Trial. Issue 4 (December 2020) - Hoffman, M.K.; Goudar, S.S.; Kodkany, B.S.; Metgud, M.; Somannavar, M.; Okitawutshu, J.; Lokangaka, A.; Tshefu, A.; Bose, C.L.; Mwapule, A.; Mwenechanya, M.; Chomba, E.; et al.
Abstract : ( Lancet . 2020;395:285–293) Preterm birth is a common cause of infant morbidity and mortality, especially in low- and middle-income countries with limited resources. Previous studies of aspirin used to prevent preeclampsia also suggested that low-dose aspirin may help lower the incidence of preterm births. However, no large-scale trial has specifically evaluated the use of low-dose aspirin initiated in early pregnancy with the primary purpose of preventing preterm birth. The aim of this study (the ASPIRIN trial) was to determine if low-dose aspirin administered daily starting in early pregnancy reduced the incidence of preterm delivery.